2020 17th International Computer Conference on Wavelet Active Media Technology and Information Processing (ICCWAMTIP) 2020
DOI: 10.1109/iccwamtip51612.2020.9317357
|View full text |Cite
|
Sign up to set email alerts
|

H3DNN: 3D Deep Learning Based Detection of COVID-19 Virus using Lungs Computed Tomography

Abstract: With the rapid spread of the novel COVID-19 virus, there is an increasing demand for screening COVID-19 patients. Typical methods for screening coronavirus patients have a large false detection rate. An effective and reliable screening method for detecting coronavirus is required. For this reason, some other reliable methods such as Computed Tomography (CT) imaging is employed to detect coronavirus accurately. In this paper, we present a 3D-Deep learning based method that automatically screens coronavirus pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This is shown in the red color lesion as an overlay image with a grayscale CT image in the background. When it comes to COVID-19 lung lesion detection and quantification in CT, Suri et al [ 217 , 218 ] have demonstrated the usage of hybrid DL (HDL) models vs. solo DL (SDL) models, exhibiting its superiority for lung lesion segmentation in CT scans. One of the most important aspects of DL is the optimization of hyperparameters during training to obtain the best performance of the DL system.…”
Section: Deep Learning For Cvd/stroke Risk Assessment In Pd Patients ...mentioning
confidence: 99%
“…This is shown in the red color lesion as an overlay image with a grayscale CT image in the background. When it comes to COVID-19 lung lesion detection and quantification in CT, Suri et al [ 217 , 218 ] have demonstrated the usage of hybrid DL (HDL) models vs. solo DL (SDL) models, exhibiting its superiority for lung lesion segmentation in CT scans. One of the most important aspects of DL is the optimization of hyperparameters during training to obtain the best performance of the DL system.…”
Section: Deep Learning For Cvd/stroke Risk Assessment In Pd Patients ...mentioning
confidence: 99%
“…Attributes of the Nodes/ p,q,∈ X (i) UX j * Attributes of Nodes * log(X (i) , X j ) (13) where X(i) and X(j) are the neighborhood hospitals located at i th and j th position which are differentiated by their unique ID.…”
Section: Blockchain-based Data Retrieval Processmentioning
confidence: 99%
“…The diagnosis of COVID-19 disorders relies heavily on clinical symptoms, epidemiological history, computed tomography (CT), and pathogenic testing. Most of the patients with COVID-19 show the same visual symptoms on CT scans as the other lung disorders (9)(10)(11)(12)(13) despite the use of a variety of radiological modalities. Symptoms of COVID-19 vary widely across individuals, and the disease is growing at an alarming rate (14).…”
Section: Introductionmentioning
confidence: 99%
“…The latest report of the World Health Organization (WHO) reveals that COVID-19 is an infectious disease that primarily affects the lungs such as SARS, giving them a honeycomb-like ap pearance [29] . Even after recovering from COVID-19, some patients have to live with permanent lung damage [30] , [31] . The first motivation of our work is to find small infected areas in the lungs due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%